'A Question of Life and Death': Conversion, Self and Identity in Swami Shraddhanand's Autobiography. Issue 2 (3rd April 2018) - Singh, Mohinder
ABSTRACT: This paper is based on a reading and an interpretation of Swami Shraddhanand's Hindi autobiography, published in 1924. In it, Shraddhanand centrally narrates the story of his conversion to the Arya Samaj and his self-transformation in the second half of the nineteenth century. Through a close reading of the conceptual terminology embedded in the text, the paper attempts to show that the conversion being narrated here cannot be understood by referring to the category of religion alone, and that the identity that the protagonist discovers for himself—his new Arya identity—is a composite civilisational-religious identity that involves transformed ideas of religion and religiosity.